Tekotok’s Digital Satire and Public Sentiment in Response to the Realities of Work in Indonesia - Fanani, Ahmad Farid (Jurnal Politik, 2025)
Inequities within Indonesia's labor system remain a prominent issue, particularly in terms of fair access and protection for all segments of the workforce. As digital media continues to evolve, critiques of labor policy are increasingly expressed through new mediums, including satirical animations. This study aims to explore how the satirical animated videos from the YouTube channel Tekotok represent critiques of labor policy using Critical Discourse Analysis (CDA) and public sentiment analysis. A mixed-methods approach is employed, combining Fairclough’s three-dimensional model for narrative analysis with the IndoBERT model to classify sentiment in 875 YouTube comments. The results demonstrate that Tekotok’s animations effectively highlight issues such as age discrimination, unrealistic recruitment criteria, and weak worker protections. Audience responses were predominantly positive, indicating the animation’s success in conveying socially relevant critique. These findings confirm that digital animation has the potential to be a powerful and participatory medium for public criticism of employment policies in the digital era.